About the Necessity of Pragmatic Decisions in the Higher Education - Ribov, Manol (Research Papers, 2014)
The issues related to the combining of high education with higher education are been discussed. The need for updating of the professional fields has been highlighted. A special attention is been paid to the restructuring of the curriculum. The need for integrating scientific knowledge in the curriculum is been justified. The necessity of improving the performance primary structural units has been proved. The values and the attitudes of students are argumentatively presented. The signs of unacceptable behaviour coming from academics are not ignored as well. The issues regarding the integrated systems and in particular building on bases system for the quality of the subsystems for intellectual capital are been discussed as well, the organizational culture, the corporate social responsibility and the business intellectual systems. In the final part of the publication some trends for the development of higher education are been pointed out.